2015
DOI: 10.1098/rspb.2014.0690
|View full text |Cite
|
Sign up to set email alerts
|

Post-determined emotion: motor action retrospectively modulates emotional valence of visual images

Abstract: Upward and downward motor actions influence subsequent and ongoing emotional processing in accordance with a space-valence metaphor: positive is up/negative is down. In this study, we examined whether upward and downward motor actions could also affect previous emotional processing. Participants were shown an emotional image on a touch screen. After the image disappeared, they were required to drag a centrally located dot towards a cued area, which was either in the upper or lower portion of the screen. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
64
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(79 citation statements)
references
References 37 publications
13
64
0
2
Order By: Relevance
“…Based on theory of embodied cognition and metaphor congruency effect, Sasaki et al (2015) hypothesized that if postdiction can also occur in emotional processing, the emotional valence of visual stimuli would be reconstructed by the subsequent “vertical” information activated by bodily movements. In their experiments, participants were instructed to move a dot on a touch panel (virtually, participants’ hand) upward, downward, leftward, or rightward after the presentation of visual stimuli representing positive, negative, and neutral emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on theory of embodied cognition and metaphor congruency effect, Sasaki et al (2015) hypothesized that if postdiction can also occur in emotional processing, the emotional valence of visual stimuli would be reconstructed by the subsequent “vertical” information activated by bodily movements. In their experiments, participants were instructed to move a dot on a touch panel (virtually, participants’ hand) upward, downward, leftward, or rightward after the presentation of visual stimuli representing positive, negative, and neutral emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the underlying mechanisms of the metaphorical, postdictive modulation of emotional valence by bodily movements ( Sasaki et al, 2015 ) have yet to be fully understood. Specifically, it remains unclear whether this effect is limited to be postdictive or can be generalized to the predictive or prospective effect.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, backward masking is also considered to be a kind of postdictive effect, showing that a masking stimulus that is presented later can suppress the visibility of a target that is presented earlier (i.e., Bakhman, 1994). In addition to these low-level simple phenomena, postdictive effect could also emerge in high-level perceptions like causality perception (Choi & Scholl, 2006) and emotional processing (Sasaki, Yamada, & Miura, 2015). Choi and Scholl (2006) demonstrated that participants perceived a collision between two objects (i.e., one ball cause the other to move) in an ambiguous display even after the moment of potential overlap for collision has already passed.…”
Section: Implications For Understanding the Postdictive Effectmentioning
confidence: 99%
“…Choi and Scholl (2006) demonstrated that participants perceived a collision between two objects (i.e., one ball cause the other to move) in an ambiguous display even after the moment of potential overlap for collision has already passed. Sasaki et al (2015) found that when participants were required to drag a dot up or down on the screen immediately after showing an emotional image, they would rate the image more positive if the dragging action was up and rate it more negative if the dragging action was down.…”
Section: Implications For Understanding the Postdictive Effectmentioning
confidence: 99%
“…Specifically, it has been argued that abstract and emotion concepts have sensorimotor properties much like concrete concepts. For example, it has been shown that there is a metaphorical association between emotionally valenced concepts and the vertical plane (e.g., Meier and Robinson, 2004 ; Meier et al, 2011 ; Sasaki et al, 2012 , 2015 ; Santiago et al, 2012 ; Marmolejo-Ramos and Dunn, 2013 ; Marmolejo-Ramos et al, 2013 , 2014 ; Xie et al, 2014 , 2015 ; Damjanovic and Santiago, 2015 ). Most of the work on the association between emotion words and the vertical axis has used visual words as typical experimental stimuli.…”
Section: Introductionmentioning
confidence: 99%